Ekaterinburg at the Turn of the 20th Century: Traditions and Innovations in the Organisation of Urban Space - Olga Nikolaevna Yakhno (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2024)
This article studies the transformations of the urban space of Ekaterinburg in the conditions of socioeconomic changes in the late nineteenth — early twentieth centuries, associated with the development of transport and industrial infrastructure, population growth, and transformation into a “model capitalist city”. Changes in the activities of citizens in the economic, sociopolitical, cultural, educational, and leisure spheres required appropriate spatial and physical design. The article identifies the most important territorial zones of concentration (clusters) of buildings and infrastructure elements that began to set the specialisation of specific parts of the city. One can distinguish a commercial and financial cluster in the western part, a medical cluster in the northwestern part, and a leisure cluster in the eastern part of the city. The key social systems — religious and educational — tended to encompass the whole city. It is also noted that during the residential development, there was no strict separation of rich and poor districts even in the city centre. The specialisation of different parts of the city centre formed during the period under consideration, continued to influence the development of the planning structure of Ekaterinburg-Sverdlovsk, consolidating a peculiar division between the financial and commercial right-bank and cultural and social left-bank parts of the city. There was little economic development of the eastern border of Ekaterinburg, the northern station area, and especially the southern districts, which was the only direction that could be occupied by residential development. However, the growth led to a disproportion, as there were no religious or educational institutions in the area. Such disproportions were among the most important challenges faced by the large urban centres of Russia, which were the driving force of late Imperial modernisation.